Diversity and abundance of mammals and aves in the Gunung Leuser National Park area, Bukit Lawang, Bahorok District, Langkat Regency, North Sumatra - Berliani, Kaniwa; Nasution, Ahmad Luthfi Abdillah; Hermansyah; Atni, Oky Kusuma; Mardhatillah, Siti; Lubis, Putri Amelia; Pardosi, Sinta R; Mustaqilla, Safira (International Journal of Ecophysiology, 2024)
Gunung Leuser National Park, located in Bukit Lawang, Langkat Regency, is renowned for its rich biodiversity, hosting a significant number of bird and mammal species. This study aimed to assess the diversity and abundance of mammals and birds in the park. Conducted from May 23 to 25, 2024, using Visual Encounter Surveys (VES) along a 1,000-meter transect, the research identified 8 mammal species with a total of 84 individuals, including Presbytis thomasi and Macaca fascicularis as the most prevalent. Additionally, 12 bird species with 87 individuals were recorded, dominated by the Hirundinidae family, notably Hirundo rustica and Hirundo tahitica. Diversity indices indicated moderate species diversity for both mammals (H' = 1.58) and birds (H' = 2.02), with high evenness (E = 0.78) in both groups, suggesting stable communities. The results highlight the park's significant biodiversity and the need for repeated surveys to refine data accuracy and enhance conservation efforts.